Propuesta de manejo de derechos municipales en la localidad de Jepelacio - Mego Aguilar, Maxsimario (2010)
This research project called thesis entitled profile managemcnt of municipe:1.! so!id waste in the town of Jepelacio 201 O has to do basicaUy all system ele Evaluation and management of municipal so lid waste of origin that has been generated in the City. J epelacio with the primary goal to aspire to be one of the healthy municipalitics of Alto Mayo, besides contributing_in the process of rrmnicipal environmental management that must be implemented on a mandatory basis as he points ta the Law af the Natianal Environmental Management N o :28245, while the law provides for the varim.ts organs and institutianal powers to be implemented·through local and regional gavernments. In this regard the district municipality af Jepelacia is firrrily convinced ta ga step by step implementing .these processes that positively impact the. quality af municipal administration as well as the pravisian of municipal services such as the issue of Collectian, Transportation and Dispasal af Salid Waste produced by our camrnunity. On the other hand, the district autharity has decided to pursue a Municipal Certification process,- which should produce technical documents, instruments for enviranmental management ancl sustentatorios elements for this purpose, since the Ministry of Environrnent today so requin~s, while true this is a medium-term process but it is good to start something in arder ta plan sustainable development Jepelacia district. With the implementation of this profile Theses are contributing significantly to strengthening the Municipal Environmental Management District, as it is in pianeering the development of environmental activities Jepelacio district.